Analysis of Farming Risks in the Integration of Corn and Peanuts in Laimpi Village, Kabawo Subdistrict, Muna Regency - Salmiati; Ilma Sarimustaqiyma Rianse; Weka Gusmiarty Abdullah (International Journal of Technology and Education Research, 2026)
This study aims to describe the farming system applied in the integration of corn and peanuts, identify the types and sources of risks, analyze the magnitude of risks, and examine the efforts made by farmers to manage these risks in Laimpi Village, Kabawo District, Muna Regency. The population consisted of 20 farmers practicing integrated farming, and due to the small size, a census method was used, meaning all farmers were included as respondents. The variables observed include risk events, sources, types, impacts, levels, and risk management efforts before and after risks occur. Data were analyzed using descriptive methods, where the first analysis described the farming system, the second identified risks at each stage of farming activities such as land preparation, planting, maintenance, and harvesting along with their causes and impacts, and the third examined farmers’ risk management strategies. The results show that risks occur at all stages of farming, with land preparation and planting categorized as moderate risk, maintenance as moderate to high risk, and harvesting as low risk. Farmers manage these risks through better farm management, pest and disease control, and the use of quality seeds to reduce losses and sustain productivity